Preparation and Characterization of Chitosan/mPEG-PCL Blended Membranes for Wound Dressing and Controlled Gentamicin Release - Brianezi,Samira Faleiros Silva (2018)
In this paper, a novel wound dressing membrane for controlled release of gentamicin (GE), while covering and protecting the wound was investigated. Chitosan (CHI) was associated with methoxy polyethylene glycol - polycaprolactone copolymer (mPEG-PCL) to prepare the blended wound dressing membranes. The use of copolymer mPEG-PCL was necessary to improve the compatibility between CHI and PCL. The association of CHI and PCL was required to control the water retention and release rate of encapsulated GE. In vitro release studies were performed with the mPEG-PCL/CHI-GE membranes in order to evaluate the effect of copolymer concentration on the kinetics of GE release and water uptake. Reduced burst release rates and swelling ratios were observed for the 1/2 and 1/4 mPEG-PCL/CHI-GE membranes. In addition, all gentamicin-loaded membranes inhibited S. aureus and E. coli growth, and demonstrated color, moisture and thermal stability. Therefore, mPEG-PCL/CHI-GE membranes showed important features for potential wound dressing and drug delivery applications.